Influence of respiratory movement during post mastectomy radiotherapy on targets and heart for breast cancer. Issue 2 (2nd June 2022) - Jeon, Hosang; Ki, Yongkan; Kim, Dong Woon; Kim, Wontaek; Nam, Jiho; Kim, Donghyun; Park, Dahl; Park, Jongmoo; Joo, Ji Hyeon
Abstract: Background/aim: This study aimed to compare the dosimetric consequences of respiratory movement in volumetric‐modulated arc therapy (VMAT) and three‐dimensional conformal radiation therapy (3D‐CRT) during postmastectomy radiation therapy, including internal mammary nodes (IMNs). Materials and methods: Respiratory motion was implemented to a phantom using a dynamic device. The plans were delivered during cranial‐caudal and ventral‐dorsal movement in 5‐mm (R05) and 10‐mm (R10) amplitudes. Results: At the IMN, the dose errors were –2.8% (R05) and –6.2% (R10) for 3D‐CRT and –4.9% (R05) and –8.5% (R10) for VMAT. The dose errors in chest wall were –.5% (R05) and –6.0% (R10) for 3D‐CRT and –1.9% (R05) and –5.3% (R10) for VMAT. The left anterior descending doses showed significantly small absolute values. The gamma pass rates of VMAT were higher than those of 3D‐CRT. Conclusions: The benefit of VMAT technique in dose distribution was maintained, except in occasional instances of large breathing motion. Abstract : The dosimetric consequences of respiratory movement during VMAT and 3D‐CRT were compared, using a phantom and a dynamic device. In postmastectomy RT, benefit of VMAT technique in dose distribution was maintained, except in occasional instances of large breathing motion.